Role of employee recruitment and selection on performance of Ethiopian electric power corporation, Mekelle Branch - Belay, Birhan Nigus; Belay, Zinabu Nigus (Goodwood Publishing, 2023)
Purpose: This study aimed to assess the impact of recruitment and selection on organizational performance. It was to find out the recruitment and selection policy or practice, the impact of recruitment and selection process, the challenges associated with the recruitment and selection practice and ways to help improve human resource planning and development. Research Methodology: The study obtained information from twenty (20) respondents from staff of the Ethiopian Electric Power Corporation in the Mekelle branch using a questionnaire. The collected data were statistically analyzed using SPSS, and the chi-square test was used to interpret the hypotheses. Results: The results indicated that the advertising of job vacancies to the general public, use of employment agents, TV, newspapers, and employee referrals is mostly the mode for recruiting potential employees, and that the method used in the recruiting and selection process was very effective. Moreover, it helped improve employee performance, and the selection and recruitment process was also characterized by many challenges. Limitations: The major limitations of this study are time constraint, crisis of COVID 19, and inappropriate fulfillment of the questionnaire by respondents. Contribution: This study suggests that potential employees should be treated fairly in the recruitment and selection processes. Moreover, employees must be constantly appraised to ensure that they improve their performance.